PENGARUH STORE ATMOSPHERE DAN VISUAL MERCHANDISING TERHADAP IMPULSE BUYING PADA MR. DIY KOTA BIMA - AZRINA SALSABILLA; ISMUNANDAR ISMUNANDAR; MUHAJIRIN MUHAJIRIN (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to determine the effect Store Atmosphere And Visual Merchandising To Impulse Buying On Mr. Diy Bima City, which is measured by the Partial test (t Test) and Simultaneous Test (F Test). The population in this study is all consumers in the Bima City Area. The sampling technique uses the method purposive sampling with a sample size of 100 people. The research results show that: 1) a. Store Atmosphere have a significant effect on Impulse Buying At MR DIY Bima City; Visual Marchandising have a significant effect on Impulse Buying At MR DIY Bima City. As well as Store Atmosphere and Visual Marchadising have a significant effect on Impulse Buying At MR DIY Bima City